2012
DOI: 10.1093/jpepsy/jss106
|View full text |Cite
|
Sign up to set email alerts
|

Stigmatization Predicts Psychological Adjustment and Quality of Life in Children and Adolescents With a Facial Difference

Abstract: Identification of stigma experiences and appropriate support may be crucial to enhancing psychological adjustment and quality of life in children with facial disfigurement.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
74
1
8

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 112 publications
(89 citation statements)
references
References 28 publications
6
74
1
8
Order By: Relevance
“…Sharing meals with others is known to have high social significance; hence, patients living with dietary restrictions experience numerous potentially stigmatising situations (Diesen et al 2014). Since perceived stigmatisation is a predictor for poorer psychological adjustment (Masnari et al 2013), it is of great importance that patients are supported in so-called stigma-handling strategies (Diesen et al 2014), such as social skills training or school-based interventions, in which peers are provided with basic information about the condition, resulting in better understanding (Sharman et al 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Sharing meals with others is known to have high social significance; hence, patients living with dietary restrictions experience numerous potentially stigmatising situations (Diesen et al 2014). Since perceived stigmatisation is a predictor for poorer psychological adjustment (Masnari et al 2013), it is of great importance that patients are supported in so-called stigma-handling strategies (Diesen et al 2014), such as social skills training or school-based interventions, in which peers are provided with basic information about the condition, resulting in better understanding (Sharman et al 2013).…”
Section: Discussionmentioning
confidence: 99%
“…This data is consistent with the fi ndings of Hunt et al (2005), who evidenced some specifi c behavioral problems in children with orofacial cleft, such as anxiety and depression, however, found no signifi cant differences regarding the types of cleft. However, some studies have found that children with orofacial clefts may present a higher degree of anxiety according to the degree of facial deformity, speech diffi culties and social relationships (Ha et al, 2013;Masnari et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Este dado é condizente com os achados de Hunt et al (2005) que encontraram alguns problemas comportamentais específi cos em crianças com fi ssura labiopalatina, tais como a ansiedade e a depressão, porém, não constataram diferenças signifi cativas quanto aos tipos de fi ssura. Todavia, alguns estudos constataram que crianças portadoras de fi ssuras labiopalatinas podem apresentar um maior grau de ansiedade quanto maior forem o grau de deformidade facial, difi culdades de fala e relacionamentos sociais também (Ha et al, 2013;Masnari et al, 2013).…”
Section: Discussionunclassified